Digital family bonds are strengthened through effective communication dynamics on YouTube in Indonesia - Arisma, Yunda Widya Rida; Aesthetika, Nur Maghfirah (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Family communication plays a critical role in maintaining healthy relationships among family members, promoting openness, support, and understanding. Effective communication strengthens family bonds, especially during shared moments such as gatherings. Specific Background: Fadil Jaidi's YouTube channel provides an intriguing case study of family communication, showcasing how members interact and resolve issues. These video interactions offer valuable insights into the dynamics of family communication, particularly in the digital age. Knowledge Gap: Despite the extensive focus on communication in family studies, few have explored how family interactions are represented in social media content, especially YouTube channels, where family moments are broadcast to the public. The role of these platforms in influencing family communication patterns remains underexplored. Aims: This study aims to describe and explain the family communication patterns that occur on Fadil Jaidi's YouTube channel, focusing on openness, support, empathy, positiveness, and equality through content analysis. Results: A qualitative content analysis of five selected videos revealed that family communication on Fadil Jaidi’s channel runs smoothly. The interactions were characterized by 24 scenes: 8 scenes showing openness, 5 scenes of support, 2 scenes of empathy, 6 scenes of positiveness, and 3 scenes of equality. These categories were identified using thematic and syntactic analysis. Novelty: This study is among the first to analyze family communication within a public YouTube context, applying Eriyanto's content analysis framework. It highlights how online platforms can both reflect and influence real-life family dynamics. Implications: The findings suggest that public displays of family communication on social media platforms, like YouTube, can serve as examples for fostering positive interactions in real-life family settings. This research contributes to the understanding of how digital platforms can be used to promote healthy communication in family contexts. Highlights: Family communication on YouTube shows openness, support, empathy, positiveness, equality. Fadil Jaidi’s videos highlight effective family interactions in everyday scenarios. The study reveals digital platforms’ role in shaping family communication dynamics. Keywords: family communication, YouTube analysis, content analysis, social media, qualitative research